2022
DOI: 10.1186/s13014-022-02174-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily dose evaluation based on corrected CBCTs for breast cancer patients: accuracy of dose and complication risk assessment

Abstract: Objectives The goal of this study is to validate different CBCT correction methods to select the superior method that can be used for dose evaluation in breast cancer patients with large anatomical changes treated with photon irradiation. Materials and method Seventy-six breast cancer patients treated with a partial VMAT photon technique (70% conformal, 30% VMAT) were included in this study. All patients showed at least a 5 mm variation (swelling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The cCBCT method has been described by Thing et al 13 . and Hamming et al., 14 where the authors performed the daily dose evaluation for the breast, thorax, and pelvis with PBS. The algorithm works in two steps: First, a CBCT‐CT joint 2D histogram is created to generate a conversion function by minimizing the joint entropy between the two images.…”
Section: Methodsmentioning
confidence: 99%
“…The cCBCT method has been described by Thing et al 13 . and Hamming et al., 14 where the authors performed the daily dose evaluation for the breast, thorax, and pelvis with PBS. The algorithm works in two steps: First, a CBCT‐CT joint 2D histogram is created to generate a conversion function by minimizing the joint entropy between the two images.…”
Section: Methodsmentioning
confidence: 99%
“…When comparing the gamma pass rates for the corrCBCT and virtCT, Thing et al found the virtCT to have significantly (p < 0.05) higher pass rates than the corrCBCT for breast, prostate, and anal/rectal sites but did not show the significance for lungs. Hamming et al [42] investigated the methods for plan recalculation for breast cancer patients treated with VMAT, and found the corrCBCT (called CBCT CC in their study) performed very similarly to the virtCT (called CT V in their study), and both were adequate for dose recalculation on breast plans. Hamming et al did note that the virtCT and its correction methods are not particularly useful for breast cancer patients, as the treated site is mostly uniform soft tissue with very few opportunities for low-density overrides.…”
Section: Image Accuracymentioning
confidence: 99%
“…Additionally, the algorithm employs a stitching technique to simulate missing tissue outside the eld of view (FOV) of the CBCT by attaching the pCT outside the FOV [20,21,24]. Early versions of the algorithm using the scripting interface of the TPS have been tested have been tested by other groups [21][22][23]. The output of the algorithm is a so called corrected CBCT (CBCT c ) which can be used for dose calculation using the CT to mass-density conversion curve of the pCT.…”
Section: Algorithmsmentioning
confidence: 99%
“…The image quality of CBCT is often lower compared to fan-beam CT and the Houns eld Units (HU) to mass-or electron density conversion cannot be directly converted between these two modalities due to the different amount of scattered radiation and the projection geometry [11,12]. Several groups have investigated different strategies to overcome this limitation of the CBCT images and showed that accurate dose calculation is feasible [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%